2018
DOI: 10.1371/journal.pone.0198743
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic level in toenails is associated with hearing loss in humans

Abstract: Arsenic (As) pollution in drinking water is a worldwide health risk for humans. We previously showed hearing loss in young people who live in areas of As-polluted drinking water and in young mice orally treated with As. In this study, we epidemiologically examined associations between As levels in toenails and hearing in 145 Bangladeshi aged 12–55 years in 2014. Levels of As in toenails, but not those in urine, were shown to be significantly correlated with hearing loss at 4 kHz [odds ratio (OR) = 4.27; 95% co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
1
7
1
1
Order By: Relevance
“…Even if several recent studies analysed the use of nails as biomarkers of different minerals and nETE and to relate their concentration to some diseases risk such as amyotrophic lateral sclerosis, children obesity, hearing loss and acute promyelocytic leukaemia (Karatela et al, 2018;Chen et al, 2018;Li et al, 2018;Xu et al, 2018;Andrew et al, 2018;White et al, 2018). In the present study, no relation was found by between nETE fingernail, dietary exposure and thyroid cancer risk.…”
Section: Study Limitationscontrasting
confidence: 65%
“…Even if several recent studies analysed the use of nails as biomarkers of different minerals and nETE and to relate their concentration to some diseases risk such as amyotrophic lateral sclerosis, children obesity, hearing loss and acute promyelocytic leukaemia (Karatela et al, 2018;Chen et al, 2018;Li et al, 2018;Xu et al, 2018;Andrew et al, 2018;White et al, 2018). In the present study, no relation was found by between nETE fingernail, dietary exposure and thyroid cancer risk.…”
Section: Study Limitationscontrasting
confidence: 65%
“…In previous studies, levels of metal elements in blood samples 25 and urine samples 26 were shown to reflect the status of acute exposure to the metal elements, while nail and hair samples were used to evaluate the status of chronic exposure to the metal elements 27,28 . In our previous study, multivariate analysis showed that significant associations of arsenic levels in toenails with heating loss were at 4, 8 and 12 kHz, while a significant association of arsenic levels in hair with hearing loss was limited to 12 kHz 19 . Hearing levels at 4 kHz and 8 kHz are known to be important for daily conversation and examinations of noise-induced hearing loss and age-related loss, respectively, while 12 kHz is an extra-high frequency and hearing ability at 12 kHz is not necessary for daily communication in humans.…”
Section: Discussionmentioning
confidence: 82%
“…Our method for hearing examination has been described and published elsewhere 1519 . Briefly, we measured hearing levels by PTA at 1, 4, 8 and 12 kHz to determine the auditory threshold of subjects at each frequency.…”
Section: Methodsmentioning
confidence: 99%
“…Multivariate analysis in our epidemiological study indicated that arsenic levels in toenails, but not those in urine, were significantly correlated with hearing levels at high frequencies (4 k Hz, 8 k Hz, and 12 k Hz) in 145 subjects aged 12-55 years in Bangladesh. Since our results in mice suggest that nail arsenic level could be an index for the arsenic level in inner ears, the level of arsenic in nails is a potential biomarker for hearing loss caused by an accumulation of arsenic in inner ears in humans [56].…”
Section: Assessments Of the Health Risks Of Arsenic For Hearingmentioning
confidence: 86%